PREVENTION AND HANDLING OF SEXUAL VIOLENCE (PPKS) ON ISLAMIC ADOLESCENTS IN JUNIOR HIGH SCHOOLS THROUGH EDUCATION AND SOCIALIZATION - halimah, siti; Aisyah, Siti; Putri Syabina, Tasya; Asda Juwita, Tri; Segarahati Barus, Eni; Fatira, Marlya; Agus, Rizal; Putri, Anita (Fakultas Ekonomi dan Bisnis Islam IAIN Kerinci, 2025)
This Program, Community Services to Educates About PPKS (Prevention and Handling of Sexual Violence) on Muslim Teenagers at Al-Washliyah Private Middle School, Kampung Lalang Village, Medan Sunggal District, Medan City, North Sumatra Aims to provide an understanding of the meaning of sexual violence, types of sexual violence, the impact of sexual violence, how to prevent sexual violence and provide an experience related to the PPKS (Prevention and Handling of Sexual Violence) Officer Unit. For the activities to run smoothly PKM, the service team conducted data collection techniques using interviews with Al-Washliyah Middle School. The solution provided is to transfer knowledge to students through the Education Seminar on PPKS (Prevention and Handling of Sexual Violence). The cost of implementing PKM activities is Rp. 421,000.00 (Four Hundred and Twenty One Thousand Rupiah). After implementing community service activities in the form of training and seminars for students, the results of the service were obtained that A lack of understanding of literacy about PPKS (Prevention and Handling of Sexual Violence) Students can be resolved through training activities so that there is an understanding of the definition of sexual violence, forms of verbal sexual violence, prevention of sexual violence, PPKS task force, sexual violence on social media and how to act if experiencing harassment. The unavailability of a division to handle PPKS (Prevention and Handling of Sexual Violence) has been overcome by proposing the formation of a unique team and training for teachers at Al-Washliyah Private Middle School. The school has responded to this well with a plan to form an exceptional team, and the PKM team also suggested tightening the rules that apply in schools and providing rewards/punishments.